A generalized weak contraction principle with applications to coupled coincidence point problems - Choudhury, Binayak S; Metiya, Nikhilesh; Postolache, Mihai (Fixed point theory and applications (Hindawi Publishing Corporation), 2013)
In this paper we establish some coincidence point results for generalized weak contractions with discontinuous control functions. The theorems are proved in metric spaces with a partial order. Our theorems extend several existing results in the current literature. We also discuss several corollaries and give illustrative examples. We apply our result to obtain some coupled coincidence point results which effectively generalize a number of established results. MSC: 54H10, 54H25.